Upaya Kepolisian Perairan Resort Biak Numfor Dalam Pencegahan Illegal Fishing - Asrul Asrul (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2020)
This study aims to identify and analyze the factors that cause illegal fishing in Biak Numfor Regency, and the efforts conducted by the Biak’s Resort Water Police Unit in its prevention. The approach used in this research is empirical juridical research. Data collection techniques used are observation, interviews and literature study. The results of the study indicate that the occurrence of illegal fishing in Biak Numfor are caused by the low economic factors of the fishing community, the lack of knowledge about the dangers and impacts of illegal fishing, and low education so they tend to think instantly without taking into account the consequences of illegal fishing. Efforts to combat illegal fishing carried out by the Biak’s Resort Water Police include preventive measures (holding legal counseling, conducting regular water patrols, collaborating with other relevant agencies) and repressive efforts (arresting and examining and enforcing the law strictly in the application of sanctions against illegal fishers.